Performance Assessment of Satellite and DACCIWA Optical Gauge Rainfall Products for the Analysis of Trends and Drivers of Rainfall Extremes in Ghana - Atia Winifred Ayinpogbilla (KNUST, 2024)
A Thesis submitted to the Department of Physics, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of DOCTOR OF PHILOSOPHY(Meteorology and Climate Science)